The organic chem lab survival manual : a student's guide to techniques - Zubrick, James W. (Hoboken, New Jersey : Wiley, 2014)
This book is the essential laboratory resource for the Organic Chemistry lab. First time students and accomplished professionals agree that Zubick's sophisticated, honest, and humorous language engages the reader as a trusted friend and provides a predictive roadmap for critical thinking about the processes and regulations necessary in the real world laboratory setting. Time tested, expansive, and articulate, Zubick's manual supports students and instructors by offering a shared confidence uniquely conductive to truly dynamic learning both in this lab and other labs to come.